The AFNETA alley farming training manual. Volume 2. Source book for alley farming research - Tripathi, B.R.; Psychas, P.J. (International Livestock Centre for Africa, 1992)
This training manual is a collaborative project of the three international agricultural centres affiliated to the network: IITA, ILCA and ICRAF. The manual draws on articles, training materials, and illustrations prepared by scientists and support staff from the three institutions. The manual is intended for use in AFNETA's training courses, at which African scientists learn how to carry out alley farming research within the framework of AFNETA's collaborative research programs. It is also intended for any person interested in practicing or experimenting with alley farming. The topics covered in Volume 2, i.e. review of current systems used to classify soils and land capabilities. It also provides an introduction to the management of the major soils in the humid and subhumid zones of tropical Africa.